THE MEANING AND SYMBOL OF COMMERCIAL BRAND REGARDING CONSUMERS, POINT OF VIEW AND INTRODUCING THE WAYS FOR CREATING THE BRAND SYMBOL (Singaporean Journal of Business Economics and Management, 2013)
Having Knowledge and ability for marketing in economic organization, is one of the most important factor for success in the rivalry. Many factors are involved in the future of economic organization In this paper, we investigate the vital role of commercial brand symbol. Meanwhile, in this research, the consumer oriented model as Aker, is used. Each commercial name has especial position and also each user has especial position. Some of the brands are put in the mind of consumers and some of them have not put in the mind of consumers yet. Now, the duty of markers is that, at first, they should investigate and understand the consumers and their position and then attention to their needs, after that establish their brand symbol basis on the personality and position of most of the consumers.